Learning and Memory of Early Childhood Tahfiz Quran: A Systematic Review - Tarmilia Tarmilia; Feby Fadjaritha; Intan Wahyu Istiqomah; Eny Purwandari; Fonny Dameaty Hutagalung (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
Some of Tahfiz houses which were built to teach memorising Quran have difficulty in choosing a method that is suitable for the psychological development of early childhood. This study aims to examine the method of memorising the Quran in terms of psychological theory. This study uses a qualitative systematic review method following PRISMA with stages: Identification; Screening; Eligibility; and Included. The three stages of reviewing journal articles are: searching for journal articles, mapping themes, and analysing based on inclusion criteria. The result is that there are two suitable methods for early childhood, namely Bayani based on the verbal mnemonic technique and Kaisa based on the mnemonic physical response. This finding is expected to be developed by further research and be useful for tahfiz houses teachers to choose the method of memorising the Quran for early childhood according to psychological development